Sosialisasi Program Mobil Curhat di Kota Bogor Tahun 2015–2017 - Hana Fitria Navratilova; Naufal Muharam Nurdin; Karina Rahmadia Ekawidyani; Ahmad Sulaeman (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Nutrition counseling is used as one of the strategies to improve nutritional status and reduce the risk of metabolic syndrome through information transfer about balanced diet. As part of the community service program, Faculty of Human Ecology, IPB University collaborated with Bogor Municipality Health Office launched a mobile health counseling services in July 2014 to increase access to health services in Bogor, Indonesia, which includes nutrition counseling, detection of non-infectious diseases, HIV detection, and family counseling. The service runs across areas in Bogor city two to three times per month, attracted approximately 50 visitors per run. The program aimed to identify the nutritional status of visitors of mobile health counseling services. Primary data collected in this program were obtained using interview and direct measurement. Counseling was initiated by obtaining age and body height data through interview, while the body weight, Body Mass Index (BMI), and total body fat was measured using a portable body composition analyzer. Based on data collected between March 2015 and November 2017 (n = 1769) showed that majority of visitors were female (61.8) with largest age group were 40 to 49 years old (23.6) followed by age group of 50 to 59 years old (20.9). Half of the clients (50.4) have a normal nutritional status (BMI 18.5–25 kg/m2), but more than half (61.3) had a percentage of total body fat above normal value. Although the results have not been able to describe the nutritional status profile of Bogor residents, it can be a reference in formulating a nutrition program suitable for healthy populations.